A review on the recent developments in the materials used for sensors. (2022) - Varshney, Sudeep; Kumar Rajput, Pushpendra; Singhal, Amit; Varshney, Gunjan
Abstract: Wireless sensor network (WSN) has evolved as an emerging technology, which provides various prospects to different applications used for communication. The WSN consist of various sensors, which communicates among themselves and outside the network also to send the data / information. Different kind of materials are used to fabricate these various types of sensors. One of the primary requisites for fabrication of a sensor for a designer is, to have the knowledge of the different kinds of sensing material suitable for these sensors. This paper discusses the recent development in the novel materials and their potential use for fabricating in different types of sensor used in various applications of wireless sensor network and systems.